Dinamika Arsitektur Masjid Jamik Ismailiyah Tanjung Beringin, 1937-1982 - Al Zufri, Al Zufri; Asari, Hasan; Siregar, Yusra Dewi (Medan Resource Center, 2024)
This research aims to describe the architectural dynamics inherited by the Bedagai Kingdom through cultural acculturation, focusing on the Jamik Ismailiyah Mosque. The mosque was founded in 1880 by Prince Ismailiyah and underwent dynamic changes in form while still maintaining its historical existence. This research uses the historical method which includes heuristics, verification, interpretation, and historiography to explore the problem in depth. Observations were made using architectural theory and diachronic theory to provide a complete picture of the architectural dynamics of the Jamik Ismailiyah Mosque in Tanjung Beringin District, Serdang Bedagai. The results showed that since the establishment of the mosque in 1880 until 1982, there were various architectural acculturations that mostly still dominated traditional Malay architectural patterns. This research reveals the dynamics and development of the mosque's architectural concept based on history and acculturation findings, including changes in the layout and additions to the mosque building, providing a complete picture of the dynamic development during the period 1937-1982.